ANALISIS SUMBANGAN MASYARAKAT PADA MUHAMMADIYAH AUSTRALIA COLLEGE - Hidayah, Siti Aminah Nur (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
ABSTRACT This article aims to analyze the contribution of community donations to the sustainability of Muhammadiyah Australia College (MAC), an Islamic educational institution in Australia supported by the Muslim community. The study is motivated by the limited funding available from government and internal resources, making community contributions a key factor for institutional sustainability. The research focuses on the role of donations in financing operations, developing facilities, and providing scholarships. This study employed a library research method by analyzing secondary data from MAC’s financial reports for the period 2020–2023 and relevant literature. The findings reveal that approximately 70% of MAC’s annual budget is sourced from community donations. These funds are allocated for operational expenses, infrastructure development, scholarships, and Islamic curriculum enhancement. Transparent financial management and a community-based approach have successfully built trust, although challenges remain in terms of fluctuating donation levels. Therefore, diversification strategies such as crowdfunding, corporate partnerships, and social enterprises are recommended. The study concludes that consistent, accountable community support is essential to MAC’s sustainability, making it a potential model for Islamic education within the Muslim diaspora in Western countries. ABSTRAK Artikel ini bertujuan menganalisis kontribusi sumbangan masyarakat terhadap keberlanjutan Muhammadiyah Australia College (MAC), sebuah lembaga pendidikan Islam di Australia yang berkembang melalui dukungan komunitas Muslim. Latar belakang penelitian ini berangkat dari keterbatasan dana pemerintah maupun internal sekolah, sehingga dukungan masyarakat menjadi faktor penentu keberlanjutan lembaga. Fokus penelitian diarahkan pada peran sumbangan dalam pembiayaan operasional, pengembangan fasilitas, serta penyediaan beasiswa. Penelitian ini menggunakan metode studi pustaka (library research) dengan menganalisis data sekunder berupa laporan keuangan MAC periode 2020–2023 serta literatur pendukung. Hasil penelitian menunjukkan bahwa sekitar 70% anggaran tahunan MAC bersumber dari donasi masyarakat. Dana tersebut dialokasikan untuk kebutuhan operasional, pembangunan sarana prasarana, program beasiswa, dan pengembangan kurikulum berbasis Islam. Transparansi pengelolaan keuangan dan pendekatan berbasis komunitas berhasil meningkatkan kepercayaan publik, meski tantangan berupa fluktuasi jumlah donasi masih dihadapi. Oleh karena itu, strategi diversifikasi pendanaan melalui crowdfunding, kemitraan korporasi, dan usaha sosial sangat direkomendasikan. Simpulan penelitian menegaskan bahwa konsistensi dukungan masyarakat yang dikelola secara akuntabel menjadi kunci keberlanjutan MAC, sekaligus dapat menjadi model pendidikan Islam bagi diaspora Muslim di negara Barat.